REPLACEMENT AND BOOK VALUE. - Hatfield, Henry Rand (The Accounting Review, 1944)
Abstract The article focuses on the issue of the advisability of discarding an old, but still usable, machine, and substituting a newer model, one faces the necessity of writing off the book value of the obsolete machine. It is always disagreeable to write off an asset. The problem has not generally been discussed in accounting texts, which, for the most part, deal with the accounting for the abandoned value, whether it should be charged to surplus, added to the cost of the new machine, or charged against current income. But while the expediency of substituting a new model machine is a problem of management, rather than of accounting, occasionally an accountant transcends the too narrow limits of his own field and discusses factors which should be considered in deciding whether the change should be made. Among these are, the ability of the owner to provide funds for purchasing the new machine, the prophetic estimate that before long the price of the new machine will be substantially lowered, or that still further improvements may be expected in the near future, the effect on income taxes, or on dividends on noncumulative stock and a possible adverse influence on the credit of the corporation, if it shows a large write-off in respect of the abandoned asset.